2020
DOI: 10.33321/cdi.2020.44.33
|View full text |Cite
|
Sign up to set email alerts
|

Scientific evidence supporting recommendations on the use of the 9-valent HPV vaccine in a 2-dose vaccine schedule in Australia

Abstract: The Australian Technical Advisory Group on Immunisation (ATAGI) updated recommendations on the use of human papillomavirus (HPV) vaccines in the Australian Immunisation Handbook in 2018, regarding the use of the recently available 9-valent (9vHPV) vaccine, Gardasil 9, and a 2-dose schedule for young adolescents for HPV vaccines. This report provides an overview of the relevant scientific evidence that underpinned these updated recommendations. The 9vHPV vaccine includes 5 HPV types (HPV 31, 33, 45, 52 and 58) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Cervarix, despite having a slightly narrower range of protection, is arguably the most a cost‐effective treatment that best suited to low‐income countries 19 . In addition to preventing 90% of high‐risk HPV infections, the tetravalent vaccine also prevented 90% of condyloma acuminatum, 20 and Gardasil 9 valent vaccine was a particle vaccine, 21 which could prevent an additional 15% of cervical cancer and up to 20% of other cervical cancer HPV‐related cancers 22 . In general, the 9‐valent vaccine offers the broadest protection, while the bivalent vaccine offers the best value for money.…”
Section: Discussionmentioning
confidence: 99%
“…Cervarix, despite having a slightly narrower range of protection, is arguably the most a cost‐effective treatment that best suited to low‐income countries 19 . In addition to preventing 90% of high‐risk HPV infections, the tetravalent vaccine also prevented 90% of condyloma acuminatum, 20 and Gardasil 9 valent vaccine was a particle vaccine, 21 which could prevent an additional 15% of cervical cancer and up to 20% of other cervical cancer HPV‐related cancers 22 . In general, the 9‐valent vaccine offers the broadest protection, while the bivalent vaccine offers the best value for money.…”
Section: Discussionmentioning
confidence: 99%
“…Those who started vaccination after 15 years should receive 3 doses, with an interval of 2 and 6 months after the first application, respectively. In 2018, the country replaced the 4-valent vaccine with the 9-valent vaccine, including being used to finalize the scheme if it had been started with the tetravalent [21]. • Referenced country: Canada.…”
Section: -Valentmentioning
confidence: 99%
“…They reported that one and two doses of the HPV-16/18 were as protective as three doses in women after 4 years follow-up. Finally, the Australian Technical Advisory Group on Immunization reported a non-inferior antibody responses after two doses given at 6 and 12 months in girls and boys aged 9-14 years compared to women (16-26 years) after three doses supporting the 2-dose schedule for adolescents of this age group [32]. A randomized, observational trial evaluating alternative nHPV vaccination schedules in young females in West Africa is still ongoing (NCT03832049).…”
Section: Efficacymentioning
confidence: 99%